2016
DOI: 10.1002/jobm.201600476
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of fatty acids and hydrocarbons inAnabaena7120 and itsntcAmutant under calcium

Abstract: Calcium being a signaling molecule and mediator of cell response, we examined the modulation in fatty acid and hydrocarbon profiles of wild type cyanobacterium Anabaena sp. PCC 7120 and its ntcA mutant under the influence of different calcium chloride concentrations (0-10 mM). Dynamic modifications in fatty acid and hydrocarbon profile were evident through GC-FID analysis of extracted lipids. In the wild type, increase in CaCl (10 mM) resulted in unsaturation of fatty acids (observed in terms of high MUFA/PUFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…A transient increase in the intracellular Ca 2+ concentration ([Ca 2+ ] i ) from a resting level of about 0.2 μM up to 4 μM free Ca 2+ was observed upon light-to-dark transitions and during temperature, salt and osmotic stress [1][2][3]. The involvement of Ca 2+ has also been established in cyanobacterial growth [4], regulation of reactive oxygen species (ROS) [5], fine-tuning of the carbon (C) and nitrogen (N) balance [6,7], heat stress acclimation [8], exopolysaccharide production [9], and fatty acid and hydrocarbon composition [10].…”
Section: Introductionmentioning
confidence: 97%
“…A transient increase in the intracellular Ca 2+ concentration ([Ca 2+ ] i ) from a resting level of about 0.2 μM up to 4 μM free Ca 2+ was observed upon light-to-dark transitions and during temperature, salt and osmotic stress [1][2][3]. The involvement of Ca 2+ has also been established in cyanobacterial growth [4], regulation of reactive oxygen species (ROS) [5], fine-tuning of the carbon (C) and nitrogen (N) balance [6,7], heat stress acclimation [8], exopolysaccharide production [9], and fatty acid and hydrocarbon composition [10].…”
Section: Introductionmentioning
confidence: 97%
“…In Anabaena cells, iron deficiency is related with symptoms such as elevated expression of isiA gene, various antioxidative enzymes and total reactive oxygen species (ROS) which suggested that iron deficiency leads to oxidative stress (Latifi et al , Kaushik et al , , ). In several microorganisms including cyanobacteria, lipids are considered as the most efficient source of storage energy and also provide insulation to delicate internal organs and hormones (Singh et al , ). In cyanobacteria, lipids constitute an essential structural part of most of the cellular membranes and exhibit tolerance to variety of stresses under different conditions (Singh et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In several microorganisms including cyanobacteria, lipids are considered as the most efficient source of storage energy and also provide insulation to delicate internal organs and hormones (Singh et al , ). In cyanobacteria, lipids constitute an essential structural part of most of the cellular membranes and exhibit tolerance to variety of stresses under different conditions (Singh et al , ). However, lipids are also a potential target of oxidative damages caused by ROS generated under oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids are synthesized from the TCA cycle intermediate acetyl CoA and the esterification of fatty acids leads to the synthesis of lipids . In addition, lipids are also known to play protective roles under various stress conditions in cyanobacteria . The first and rate limiting step of fatty acid biosynthesis is known to be catalyzed by acetyl CoA carboxylase (ACCase) enzyme.…”
Section: Introductionmentioning
confidence: 99%